The Roles of Forest in Environment Modification - Nwafor, O.E.; Adepoju, S. O.; Jauro, A.G.; Mmadu, D.U. (Richtmann Publishing, 2012)
By the late 1990s the environmental problems included the greenhouse effect and global warming, thehole in the ozone layer, acid rain, and the destruction of tropical forests. But whilst the problems appear tobe largely physical (environmental), the causes and solution lie more in people’s attitude, values andexpectation. It is expected that the environment should be all things to all people (It is to be life supporting,it is to be useful, and it is to be beautiful). Unfortunately the environment cannot meet all these needs atthe same time. Cutting trees from large areas (deforestation) without adequate replanting has resulted toalmost half of the world’s tropical forest being cleared. Each year about 170,000 square kilometers of theseforests are cut and equivalent portion is degraded. Within 30-50 years there may be little of these forestsleft, many of the remaining diverse, old-growth forests are being cleared and replaced with single speciestree farms (plantations), greatly reducing wild life habitats and biodiversity. Eliminating or decimating wildspecies through destruction of habitats, commercial hunting, pest control and pollution. Each yearthousands of wild life species become extinct, mostly because of human activities. If habitat destructioncontinues at present rates, as many as 1.5 million species could disappear over the next 25 years - drasticloss of vital earth capital, polluting renewable air, and water and soil so that they are unusable. This worktherefore, x-rayed the benefits of forests to the environment, the concept of environmental sustainabilityand management of forests to enhance functional environment.